EFFECT OF WEED CONTROL STRATEGIES ON PROXIMATE COMPOSITION OF MAIZE, COWPEA, AND THEIR INTERCROP - Lawal, A. R.; Olayinka, B. U.; Etejere, E. O.; Abdulra'uf, L. B. (FUDMA JOURNAL OF SCIENCES, 2022)
Weed interference causes low land-use efficiency, expensive cost of production, related to control of plant and pests, low quality of crops and high cost and less efficient utilization of labour. The increase in herbicide resistance weeds which has led to increase use of herbicide has been a great concern to human health. This necessitated the need to investigate the effect of pendimethalin (P) with supplementary hand weeding (HW) on weed control efficiency and proximate composition of maize, cowpea and their intercrop. Field experiments were carried out in 2017 and 2018 rainy seasons. The field layout followed complete randomized block design with three replicates. There were eight treatments: Sole Maize/Cowpea + P, Sole Maize/Cowpea + P + 1HW at 3 weeks after sowing (WAS), Sole Maize/Cowpea + P+ 2HW at 3 and 6 weeks after sowing (WAS), Sole Maize/Cowpea weedy check, Intercrop + P, Intercrop + P + 1HW at 3WAS, Intercrop + P + 2HW at 3 and 6 WAS and Intercrop weedy check. It was observed that, P+1HW and P+2HW significantly (pâ‰¤0.05) increased carbohydrate (3.61%, 5.61%, 3.73% and 5.75%), protein (13.30%, 15.20%, 5.78% and 14.62%) and lipid contents (60.25%, 87.46%, 56.61% and 64.87%) in maize, cowpea and their respective intercrop. It can be concluded that the use of pendimethalin and 1 supplementary hand weeding effectively suppress weed-crop competition and increase the proximate composition of maize and cowpea